2018
DOI: 10.1016/j.jmii.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of EV71 3C polymorphisms with clinical severity

Abstract: We found that 3C polymorphisms were associated with clinical severity and viral replication, which might be related to 3C interaction with important host proteins such as TRIM21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In addition, the mutations in P3 region have been reported to impact on neurovirulence. For example, the polymorphism of EV71 3C at the 79th AA was shown to be associated with clinical severity . The T79V mutant caused the most severe clinical presentations as compared with other T79I and T79A mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mutations in P3 region have been reported to impact on neurovirulence. For example, the polymorphism of EV71 3C at the 79th AA was shown to be associated with clinical severity . The T79V mutant caused the most severe clinical presentations as compared with other T79I and T79A mutants.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, nonstructural proteins 2A and 3C are the key proteases in the EV71 proliferation process and are closely related with clinical severity. 14,[52][53][54] Because nonstructural proteins have been regarded as drug targets, 55,56 we cloned the 2A and 3C genes separately into the pFlag-CMV-2 vector to investigate whether LJ04 exerts an effect on protease activity. In this assay, eIF4G, which is a substrate of both 2A and 3C, was employed as the indicator, 57,58 and β-actin was used as the control.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the time‐of‐addition and penetration assays both suggest that LJ04 also exerts an inhibitory effect after EV71 entry into cells, and thus, we investigated the targets of LJ04. To our knowledge, nonstructural proteins 2A and 3C are the key proteases in the EV71 proliferation process and are closely related with clinical severity . Because nonstructural proteins have been regarded as drug targets, we cloned the 2A and 3C genes separately into the pFlag‐CMV‐2 vector to investigate whether LJ04 exerts an effect on protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the 69th residue of 3C pro has been identified as a novel virulence determinant of EV-A71 (Li B. et al, 2017 ). Ma et al recently confirmed that the polymorphisms of EV-A71 3C pro at the 79th amino acid position were associated with clinical severity and viral replication, which might be related to the interaction of 3C pro with important host proteins such as tripartite motif-containing protein 21 (TRIM21) (Ma et al, 2017 ). EV-A71 3C pro could interfere with the polyadenylation of host mRNA by digesting the host protein CstF-64, a cleavage-stimulating factor responsible for 3′pre-mRNA cleavage and polyadenylation (Weng et al, 2009 ).…”
Section: Introductionmentioning
confidence: 94%